(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the significance of artificial intelligence (AI) in daily life, highlighting its role in transforming various sectors such as healthcare, education, transportation, and entertainment. AI technologies are now embedded in routine tasks, improving efficiency, personalization, and decision-making. This study provides an overview of AI applications and their impacts, using a structured approach to examine the current literature, research methods, and results from real-life case studies.